Contribution of Flexibility and Agility Towards Dribbling Ability of CIP Fc Karawang Football Players - Maulana, Deni; Gemael, Qorry Armen; Dewi, R. Retna Kinanti; Izzudin, Deden Akbar; Aulia, Dany (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This study aims to analyze the contribution of two physical conditioning factors, flexibility and agility, to the dribbling ability of football players at CIP FC Karawang. A correlational method was employed, with a sample of 25 players. Data collection was conducted through a series of tests: the sit and reach test to measure flexibility, the dodging run test to assess agility, and a dribbling test to evaluate players' dribbling skills. The correlation analysis indicated that flexibility had a correlation coefficient of 0.348 with dribbling ability and a significance level of 0.089. Although a positive relationship was found, this significance level exceeds 0.05, meaning the correlation between flexibility and dribbling is not statistically significant. Conversely, agility showed a very strong correlation with dribbling, with a correlation coefficient of 0.909 and a significance level of < 0.001, indicating a highly significant relationship. The coefficient of determination revealed that flexibility accounted for only about 12.10% of the variation in dribbling ability, whereas agility accounted for up to 82.63% of the variation. When combined, flexibility and agility explained approximately 84.1% of the variation in dribbling ability. In conclusion, agility has a significantly greater and more impactful contribution to dribbling ability than flexibility. Therefore, to enhance players' dribbling skills, training should primarily focus on improving agility, while flexibility can be maintained as a supportive factor to prevent injuries and aid player mobility. This study is expected to serve as a reference for coaches and players in developing effective training programs to improve dribbling skills.